The hemingway thief eaudiobook - Harris, Shaun (Tantor Media, 2016)
Novelist Henry "Coop" Cooper is contemplating a new book between sipping rum and lounging on a Baja beach with hotel owner Grady Doyle. When Grady tries to save a drunk from two thugs, Coop tags along for the sake of a good story. The drunk is Ebbie Milch, a small-time thief on the run in Mexico because he has stolen the never-before-seen first draft of Ernest Hemingway's A Moveable Feast from a wealthy rare book dealer. The stolen manuscript is more than just a rare piece of literary history. It reveals clues to an even bigger prize: the location of a suitcase the young, unpublished Hemingway lost in Paris in 1922. A year's worth of his stories had vanished, never to be seen again. Until now. But Coop and Grady aren't the only ones with their eyes on this elusive literary prize, and what starts as a hunt for a legendary writer's lost works becomes a deadly adventure. For Coop this story could become the book of a lifetime . . . if he lives long enough to write it.